Paws for a cause - May, Kyla (May, Kyla. Diary of a pug, 2020)
When the local animal shelter can't afford new toys, it's up to Bub and his human, Bella, to save the day. But how could they possibly raise the money? A pet wash, of course! Fun and high jinks abound as Bella and Bub learn that running a pet wash is harder and wetter than it looks. With full-color artwork throughout, this funny and charming diary-format early chapter book is perfect for anyone who believes a furry pal is the best kind of friend.